Merger and acquisition: the organization well being and impact to the employees of the acquired organization / Roshidi Hassan - Hassan, Roshidi (Institute of Business Excellent and University Publication Center (UPENA), 2010)
The paper aims to discuss the types of mergers and acquisitions and elaborate on the effectiveness of the integration of the merger based on the previous research done. Merger and acquisition do have significant impacts to employees well being, work, team performance and organization performances. Managing acquisition process and the employees of the acquired organization in the right manner and approaches can reduce the negative impact of the acquisition process. It also can help organization to recover and perform again in shorter span of time. Organization should employ the right approach and strategies during the acquisition process and special attention given to effectively managing the employees of the acquired organization. The significance of the paper stems from the fact that it highlighted some important points that need to be considered by organizations when implementing merger and acquisition exercises based on the reviews of earlier studies and some from authors own viewpoints.